Littératie et activités médiatisantes à l'école primaire : pour reconsidérer les modalités d'enseignement et d'apprentissage - Pascal Dupont (Nantes Université, 2017)
Building on the broad epistemological orientations of the concept of literacy and its French approach, it will, in this article, consider how it can contribute to the study of mediation activities and renewal educational modalities teaching and learning in French primary school. In this perspective we are wondering about the different types of oral and written reflexive and on the principles of their organization and their use in a participation framework to focus student's attention on objects of knowledge. The more specific purpose of our study is to compare their role in first year of kindergarten and fifth grade classe in French-language sequence to determine whether they may have similar role regardless of class level.